Determinant Factors Of Caesarean Section Delivery In Central Java (SDKI Data Analysis) - Wibowo, Syifa Sofia; Wulan, Widya Ratna; Wulandari, Respati; Pantiawati, Ika; Salsabila, Dinar Indri Bakti (Health Science UDINUS, 2025)
Central Java Province continues to hold the third-highest MMR in Indonesia as of 2023. Caesarean section births are maternal services associated with rates of maternal and newborn morbidity and mortality. The purpose of this study is to examine the factors influencing Caesarean section births in the province of Central Java. The 2017 Indonesian Demographic Health Survey (IDHS) provided the data used in this investigation. 1,060 data were gathered after sorting, and total sampling was employed. SPSS was used to analyze the data, utilizing the frequency distribution for univariate analysis and the Pearson Product Moment test for bivariate analysis. Mothers between the ages of 26 and 28 who have two children, have not given birth in the past year, have a middle-class income, have no problems during childbirth, have neither high blood pressure nor low blood pressure, and whose kids are not breech are the data mode based on study data. Every circumstance influences the decision to use a caesarean section as a delivery procedure. The family's financial situation has the biggest impact on the variable of caesarean delivery.